Transaction costs of construction enterprises in foreign economic activity - Rubtsova О (Ways to Improve Construction Efficiency, 2020)
The article proposes amendments to the existing regulations to reflect the costs associated with the entry of domestic construction enterprises into foreign markets to prevent the decline of business entities in Ukraine and, accordingly, the outflow of highly skilled labor from the country. The term "transaction costs", introduced in circulation in 1937 by R. Coase in the work "Nature of the firm" is considered. It is determined that many domestic and foreign authors dealt with the issues of accounting for transaction costs, but to date, even there has not been a consensus on the classification and reflection of such costs in the enterprise. In order to effectively introduce Ukrainian construction companies into the external economic space and, accordingly, reduce the outflow of skilled labor from the country, it is necessary to solve the issues of accounting reform and cost sharing of enterprises (transaction costs). in establishing joint ventures for construction abroad. There is a problem of accounting for transaction costs in order to "calculate the cost" of enterprises entering the external markets of construction services and to start cooperation with foreign partners and to sign agreements on joint activities. The accounting proposals for accounting of such expenses are considered, namely: creation of a separate account in the 9th class of the plan of accounting accounts "Costs of activity", identification with representative expenses in the composition of accounts 92 "Administrative expenses" and 93 "Costs of sales" and other accounts of 9th class , commissioning of the Transit Account 86 "Transaction Expenses" "with the further assignment to Class 9 accounts by functional purpose". In order to enhance the integration of construction companies in the global economic space, the creation of joint ventures requires the legislative definition of the term "transaction costs" in both domestic and international standards and IFRS and to develop a unified approach to accounting for such costs in the legislation of Ukraine and to amend the accounting plan accounts.